Corporate venture capital: global trends and evaluation of russia’s prospects - О. A. Yeremchenko (Ekonomika Nauki)
The article analyzes the global trends of corporate venture financing (CFE) as a whole and for individual sectors of the economy. It is shown that the industries in which KFW is most actively and dynamically used are the Internet, mobile communications and healthcare. The maximum attention of corporate venture funds is attracted by start-ups in the early stages of raising capital, more than half of all venture capital deals are made at the Seed / Angel (seed stage) and Early Stage stages (the second stage of attracting start-up capital). The most common exit from venture capital deals during 2014–2018. For most industries, the redemption share of the FAC is a management startup (Management Buyout). It was concluded that Russia is poorly included in the use of corporate venture capital as a tool for building technological capacity: the country’s share in the number of corporate venture capital transactions in 2018 is 1.9% of the global total, and the total investment of Russian enterprises estimated at only 0.45% of the global total. It was suggested that it would be expedient to increase the activity of Russian corporations in the field of creating and using the capabilities of the FSC.